A Novel Two-Step Spin-Coating Process for Preparing PEDOT/PSS thin Films and Review of Recent Advances in Spin Coating - Cheng, Wen-Zhen; Liu, Jin-Xia; Mei, Yin-Ang; Zhang, Ping; Omi, Takuya; Takigami, Yuki; Zhang, Ke; Okuzaki, Hidenori; Yan, Hu (Recent Patents on Materials Science, 2015)
We systematically investigated the influence of surfactant on processing PEDOT/PSS thin films by spin-coating technique. As a result, the conductivity of the PEDOT/PSS thin films prepared by the two-step spin-coating method was to be averagely ca. 400Scm-1 which was calculated with sheet resistance and thickness. On the other hand, the conductivity of the PEDOT/PSS thin films prepared by the one-step spin-coating method should be much lower than that of two-step one if assuming that the thickness is the same for the two methods. It is considerable that in the one-step spin-coating method, aggregation of PEDOT/PSS colloidal particles easily occurs before spin-coating, resulting in inhomogeneous coating film. Such inhomogeneous film would show lower conductivity. The two-step spin-coating method can avoid the aggregation and then result in homogeneous film and higher conductivity. Reviews of recent patents on wet-process techniques reported by other research groups are also reported.
Keywords: surfactants